2019
DOI: 10.1007/s13300-019-0643-1
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Multicenter Evaluation of Quality of Life and Treatment Satisfaction in Type 2 Diabetes Patients Receiving Once-Weekly Trelagliptin Versus a Daily Dipeptidyl Peptidase-4 Inhibitor

Abstract: Introduction Dipeptidyl peptidase-4 (DPP-4) inhibitors are an established treatment in type 2 diabetes mellitus (T2DM). The objective of this study was to investigate differences in quality of life (QOL) and treatment satisfaction among treatment-naïve T2DM patients receiving once-weekly trelagliptin or a daily DPP-4 inhibitor. Methods In this multicenter, randomized, open-label, parallel-group, phase IV study conducted in Japan, 218 patients were randomized to trelagli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
(30 reference statements)
0
5
0
Order By: Relevance
“…DTR-QOL is a diabetes-specific QOL questionnaire [25]. Previous studies have demonstrated that both SGLT2is [29,30] and DPP4is [31,32] improve scores in DTR-QOL. The results of this study showing a significant improvement in DTR-QOL scores in both groups were consistent with the findings of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…DTR-QOL is a diabetes-specific QOL questionnaire [25]. Previous studies have demonstrated that both SGLT2is [29,30] and DPP4is [31,32] improve scores in DTR-QOL. The results of this study showing a significant improvement in DTR-QOL scores in both groups were consistent with the findings of previous reports.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of treatment scales used to evaluate the efficacy of the intervention were a general purpose scale (MTBQ) in one article [ 38 ], and disease-specific scales in ten studies: two used the Cystic Fibrosis Questionnaire-Revised (CFQ-R) [ 39 , 40 ], two used the Treatment-Related Impact Measures for Diabetes (TRIM-D) [ 36 , 41 ], two used the Diabetes Medication Satisfaction questionnaire (DiabMedSat) [ 35 , 42 ], one used the Diabetes Therapy-Related Quality of Life (DTR-QoL) questionnaire [ 37 ], and two used ad hoc questions [ 43 , 44 ]. For some scales, a higher value corresponded to a higher burden, whereas for others, it was the opposite.…”
Section: Resultsmentioning
confidence: 99%
“…Among the seven studies that investigated a drug-based intervention, four assessed whether an intervention decreasing dosing frequency could have a lesser impact on patients’ lives [ 36 , 37 , 39 , 42 ]. Significant positive results were found in three studies, two of which were conducted in diabetic patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DTR-QoL is a Japanese-specific measure of HRQoL that has been extensively employed in studies of glucose-lowering medication, including several involving GLP-1RAs [ 33 35 ], dipeptidyl peptidase-4 inhibitors [ 36 38 ], and the SGLT2i ipragliflozin [ 39 ]. As in the current trial, the questionnaire has shown a high sensitivity for detecting and measuring diabetes-related HRQoL compared with, for example, the EQ-5D questionnaire [ 40 ].…”
Section: Discussionmentioning
confidence: 99%